Methylenetetrahydrofolate Reductase CpG Islands: Epigenotyping. Issue 4 (25th June 2015) - Wei, Loo Keat; Sutherland, Heidi; Au, Anthony; Camilleri, Emily; Haupt, Larisa M; Gan, Siew Hua; Griffiths, Lyn R
Abstract : Background: Determination of the differential DNA methylation patterns of methylenetetrahydrofolate reductase ( MTHFR ) that are associated with differential MTHFR activity is important to understand the pathogenesis of ischemic stroke. However, to date, no data are available on the differential DNA methylation profiles of Kelantanese Malays. Therefore, we developed a rapid and efficient serial pyrosequencing assay to determine differential DNA methylation profiles of MTHFR, which help to further our understanding of the pathogenesis of ischemic stroke. The developed assay also served as the validation platform for our previous computational epigenetic research on MTHFR . Methods: Polymerase chain reaction primers were designed and validated to specifically amplify the cytosine that is followed by guanine residues (CpGs) A and B regions. Prior epigenotyping on 110 Kelantanese Malays, the serial pyrosequencing assays for the CpGs A and B regions were validated using five validation controls. The mean values of the DNA methylation profiles of CpGs A and B were calculated. Results: The mean DNA methylation levels for CpGs A and B were 0.984 ± 0.582 and 2.456 ± 1.406, respectively. The CpGs 8 and 20 showed the highest (5.581 ± 4.497) and the lowest (0.414 ± 2.814) levels of DNA methylation at a single‐base resolution. Conclusion: We have successfully developed and validated a pyrosequencing assay that is fast and can yield high‐quality pyrograms for DNA methylation analysis and is therefore applicable to high throughput study. Using this newly developed pyrosequencing assay, the MTHFR DNA methylation profiles of 110 Kelantanese Malays were successfully determined. It also validated our computational epigenetic research on MTHFR .